Bureaucrats as Innovators? Statistical Analysis on Innovative Capacity within the Hungarian Central Civil Service - Marton GELLÉN (Transylvanian Review of Administrative Sciences, 2016)
What makes a public administration innovative if it is strongly legalistic and profoundly bureaucratic? Are there innovators in such a setting who would be able to elaborate strategies in accordance with public demands? If yes, who are the innovators and what are they like? Are they among the leaders? The article offers an answer to these questions based on an empirical research conducted in Hungary where public administration is not only legalistic but has a strong culture of topdown domination. The current study targets the key element of innovativeness namely: managerial and cultural prerequisites of innovation within central public administration. The empirical research was carried out in the Hungarian central civil service. The article also discusses whether such an environment would have an impact on innovations. According to the fi ndings of the article, certain prerequisites of an innovative environment exist in the given strictly hierarchic, traditionally stiff setting; however, traits of innovativeness can be identifi ed in innovators who are genuine bureaucrats at the same time.